2013
DOI: 10.1016/j.actbio.2013.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Hollow hydroxyapatite microspheres: A novel bioactive and osteoconductive carrier for controlled release of bone morphogenetic protein-2 in bone regeneration

Abstract: The regeneration of large bone defects is a common and significant clinical problem. Limitations associated with existing treatments such as autologous bone grafts and allografts have increased the need for synthetic bone graft substitutes. The objective of this study was to evaluate the capacity of novel hollow hydroxyapatite (HA) microspheres to serve as a carrier for controlled release of bone morphogenetic-2 (BMP2) in bone regeneration. Hollow HA microspheres (106–150 μm) with a high surface area (>100 m2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 42 publications
5
75
1
1
Order By: Relevance
“…The G-HA group was similar to the clinical OS group, but exhibited denser and stronger structures than those of the OS group. A higher percentage of the bone island was present in the G-HA scaffold, which revealed greater osteoconductivity than either F or OS treatment [38][39][40]. Fig.…”
Section: Assessment Of Bone Regenerationmentioning
confidence: 91%
“…The G-HA group was similar to the clinical OS group, but exhibited denser and stronger structures than those of the OS group. A higher percentage of the bone island was present in the G-HA scaffold, which revealed greater osteoconductivity than either F or OS treatment [38][39][40]. Fig.…”
Section: Assessment Of Bone Regenerationmentioning
confidence: 91%
“…Our results are supported by previous in vivo studies that demonstrated the bone regeneration effect of BMP-2. Xiao et al 23 used BMP-2 loaded hollow hydroxyapatite microspheres coated with PLGA to repair calvarial defects of rats, inducing significantly enhanced bone regeneration. Similar findings were revealed in studies on rats, [36][37] mice, 24 and sheep.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Recently, an enhanced effect of BMP-2 on bone regeneration was in animal studies. [23][24][25][26] In a previous study, we achieved sustained release (over $1 month) of rhBMP-2 from rhBMP-2-loaded poly(-lactic-co-glycolic acid) (PLGA) microspheres. 27 Alkyl cyanoacrylates are used as biological adhesives due to convenience, excellent bond strength, and rapid solidification.…”
mentioning
confidence: 99%
“…Recently, microspheres have been proposed as a means of local drug delivery and have achieved markedly elevated pharmacological effects while minimizing systemic administrationassociated toxic effects [2,3]. In the field of bone-related materials, an ideal system for bone regeneration should simultaneously function as a controlled local delivery device for drugs or growth factors and as an osteoconductive graft to support bone formation [4,5].…”
Section: Introductionmentioning
confidence: 99%